2013
DOI: 10.1103/physrevb.88.115206
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic instability induced by Rh doping in the Kondo semiconductor CeRu2Al10

Abstract: The magnetic ground state of the Rh-doped Kondo semiconductor CeRu 2 Al 10 [Ce(Ru 1−x Rh x ) 2 Al 10 ] is investigated with the muon spin relaxation method. Muon spin precession with two frequencies is observed in the x = 0 sample, while only one frequency is present in the x = 0.05 and 0.10 samples, which is attributed to the broad static field distribution at the muon site. The internal field at the muon site is enhanced from about 180 G in the x = 0 sample to about 800 G in the Rh-doped samples, supporting … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 30 publications
2
23
0
Order By: Relevance
“…(2) is the Kubo-Toyabe term, which accounts for the dip seen in the µ + SR spectra near 5.5 µs even in the magnetically ordered state, indicating that the internal field seen by the muons on this site is smaller than that of the nuclear field. This suggests that the corresponding muon site can be assigned to the 4a crystallographic position [27].…”
Section: Muon Spin Relaxationmentioning
confidence: 94%
“…(2) is the Kubo-Toyabe term, which accounts for the dip seen in the µ + SR spectra near 5.5 µs even in the magnetically ordered state, indicating that the internal field seen by the muons on this site is smaller than that of the nuclear field. This suggests that the corresponding muon site can be assigned to the 4a crystallographic position [27].…”
Section: Muon Spin Relaxationmentioning
confidence: 94%
“…Furthermore, m AF is easily rotated from c to b or from c to a axis by a small magnetic field, a small amount of Ce-or Ru-site substitution and pressure, etc. [27][28][29][30][31][32][33][34][35][36][37][38][39][40]. (5) The spin gap and also charge gap appear in the AFM-ordered phase, whose origin has not yet been clarified [6,[40][41][42][43][44][45][46][47][48][49][50][51][52][53].…”
Section: Introductionmentioning
confidence: 99%
“…11 Recently Guo et al 28 have investigated Ce(Ru 1−x Rh x ) 2 Al 10 (x = 0−0.08) series using muon spin relaxation and their dipolar fields calculation supports the 4c position, while for the 4a one, these authors found almost zero internal field.…”
Section: 1112mentioning
confidence: 99%